Estimation of tungsten and ODS tungsten damages after dense plasma exposure in PF-12 and PF-1000 - Shirokova, V.; Laas, T.; Priimets, J.; Demina, E.V.; Prusakova, M.D.; Sholtz, M. (Вопросы атомной науки и техники, 2012)
The paper presents experimental investigations of damages in pure tungsten and ODS (oxide dispersed strengthened) tungsten under dense plasma shots. The experiments were performed with plasma focus devices PF-12 and PF-1000 with a power flux density of 10⁶…10¹² W/cm² using deuterium. The surface morphology of the targets exposed to plasma streams is analyzed using electron and optical microscopy. Due to the plasma effect, different surface structures, such as wave-like structures, a melted layer, a mesh of microcracks, droplets, craters, crevices and holes appear. Both the original and irradiated samples were investigated by local X-ray spectroscopic analysis and by X-ray phase-shift analysis. Представлены результаты исследований повреждений в чистом вольфраме и вольфраме, легированном дисперсными, оксидами под воздействием плотной плазмы. Эксперименты были проведены на установках плазменный фокус ПФ-12 и ПФ-1000 в дейтериевой плазме с плотностью мощности 10⁶…10¹² W/cm². Морфология поверхностей мишеней, облученных плазменными потоками, была исследована с помощью сканирующего электронного микроскопа и оптического микроскопа. На поверхности материала были обнаружены различные дефекты, такие как расплавленный слой, волнообразные структуры, сеть микротрещин, брызги, кратеры, наплывы и поры. Оба материала до и после облучения также исследовались с помощью рентгеноспектрального и рентгеновского фазового анализов. Представлені результати досліджень пошкоджень у чистому вольфрамі та вольфрамі, легованому дисперсними, оксидами під впливом густої плазми. Експерименти були проведені на установках плазмовий фокус ПФ-12 та ПФ-1000 на дейтерієвій плазмі з густиною потужності 10⁶…10¹² W/cm². Морфологія поверхонь мішеней, опромінених плазмовими потоками, була досліджена за допомогою скануючого електронного мікроскопа та оптичного мікроскопа. На поверхні матеріалу були виявлені різні дефекти, такі як розплавлений шар, хвилеподібні структури, сітка мікротріщин, бризки, кратери, напливи і пори. Обидва матеріали до і після опромінення також досліджувалися за допомогою рентгеноспектрального й рентгенівського фазового аналізів.